Demographic Influences on Budget-Conscious Nutrition: A Study of Age and Gender Impacts on Food Choices - Yash, Panchal; Goyal , Vikas; Thakur, Aryan; Chauhan, Rahul; Maseleno, Andino (Siber Journal of Advanced Multidisciplinary, 2024)
This study explores the impact of age and gender on food budgeting behaviors, focusing on strategies individuals use to maintain balanced nutrition under financial constraints. Through an ANOVA analysis, findings indicate that age does not significantly affect food budgeting habits, while gender shows a significant influence on the types of food bought when budgeting, suggesting different dietary priorities. These insights contribute to a better understanding of how demographic factors shape food choices, essential for developing targeted nutrition and budget management programs. With rising global food prices and economic disparities, these findings are particularly relevant for policymakers and health organizations aiming to promote affordable, healthy eating practices. Future research should consider additional demographic variables and the role of environmental factors to broaden these insights and support global food security efforts.